2008
DOI: 10.2174/138955708783331577
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of COX-2 Inhibitors

Abstract: The two isoforms of enzyme cyclooxygenase viz. COX-1 and COX-2 play key roles in the metabolism of arachidonic acid. The enzyme COX-2, when over expressed, leads to more production of prostaglandins causing inflammation and it also participates in the propagation of cancer. Therefore, COX-2 becomes the cellular target of a number of chemical entities for the treatment of inflammatory diseases as well as for the chemotherapy of cancer. In the present review, an up to date status of the compounds investigated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Inflammation is the main etyological factor in oral squamous cell carcinoma (OSCC), COX-2 activity is related both to inflammation and carcinogenesis and its expression has been found increased in OSCC together with other pro-inflammatory molecules as inducible nitric oxide synthase (iNOS) and vascular endothelial growth factor (VEGF); overexpression of these markers was also associated with limph node metastasis, tumor staging and grading [25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is the main etyological factor in oral squamous cell carcinoma (OSCC), COX-2 activity is related both to inflammation and carcinogenesis and its expression has been found increased in OSCC together with other pro-inflammatory molecules as inducible nitric oxide synthase (iNOS) and vascular endothelial growth factor (VEGF); overexpression of these markers was also associated with limph node metastasis, tumor staging and grading [25][26].…”
Section: Discussionmentioning
confidence: 99%
“…19) Most of them have high lipophilicity. Indomethacin is a traditional non-selective inhibitor of the COX isozyme which is widely used as a NSAID, but with poor brain penetration largely due to the presence of the carboxylic acid moiety.…”
Section: )mentioning
confidence: 99%
“…The discovery of the speciic role of COX-2 enzyme in inlammation resulted in the development of several COX-2 selective inhibitors to overcome the GI side efects of classical NSAIDs [15,16]. Interestingly, before the conirmation of existence of COX-2 enzyme, the DuPont company discovered a compound Dup-697 (Figure 2) as a potent anti-inlammatory agent without having the ulcerogenic efects of NSAIDs [17].…”
Section: Progress In the Pursuit Of The Development Of Cyclooxygenasementioning
confidence: 99%
“…Furthermore, recent studies revealed the association of COX-2 with various other pathophysiological processes such as Alzheimer's disease, Parkinson disease, schizophrenia, epilepsy, depression, diabetic peripheral neuropathy and various cancers. [15,16]. The recognition of new roles for COX-2 selective inhibitors imposed a great challenge to the researchers to design and explore alternative scafolds to develop COX-2 selective inhibitors with improved potency and eicacy in order to circumvent various side efects associated with the currently available NSAIDs.…”
Section: Introductionmentioning
confidence: 99%